Effect of parasitic copepods on the growth of Abramis brama fish from Beni-Haroun dam of Mila city (Northeast Algeria) - Barook, H; Sahtout, F; Kaouachi, N; Boualleg, C. (My University, 2021)
The growth parameters are valuable data to provide a good understanding on the general biology and the population dynamics of fishes, as well as enable to establish the mathematical models to compare the growth curves, and subsequently to perform the demographic analyses. Thus, the present work was undertaken to study the effect of two parasitic copepods, namely Ergasilus sieboldi and Ergasilus briani on the growth of 141 fish individuals of Abramis brama species from Beni-Haroun dam of Mila city (northeast Algeria). Herein, the study was conducted on 141 fish individuals during the period July 2015-October 2016. The age of fishes was determined by scalimetric method since the fish sex was macroscopically determined where the number of females was found very higher (97) than that of males (44). Moreover, the fish growth study was performed according to the mathematical method of Von Bertalanffy (1938). The determined growth parameters in Abramis brama fish affected by the two parasitic copepods showed that the non-parasitized host fishes present the following growth values: L∞=40 cm; K=0,30; t0=-0,29; Ø’=2,68, while the growth values of the parasitized host fishes are L∞=30 05 cm; K=0,31; t0=-0,27; Ø’=2,48. Hence, these parasites slow down the absolute growth in length of the parasitized fishes, which in turn suffer the decline in their K condition index (K=0,10) compared to non-parasitized fishes (K=0,22). Further, the evolution of the studied total fish weight in relation to their size exhibits a negative (minor) allometry (b<3) for the non-parasitized and parasitized specimens (without distinction between both sexes).